DETECTION OF FIVE VIRUS INFECTIONS IN THE LAYER FARM WITH RUNTING-STUNTING SYNDROME IN SUKABUMI AND TANGERANG USING POLYMERASE CHAIN REACTION TECHNIQUE - Risza Hartawan; Ni Luh Putu Indi Dharmayanti (Universitas Syiah Kuala, 2017)
The objective of this study was to identify the five different viral infections including avian influenza, Newcastle disease, avian reovirus, avian encephalomyelitis, and Marek’s disease in the runting-stunting syndrome outbreak in several commercial layer farms in Sukabumi and Tangerang in November 2014 using polymerase chain reaction technique. As results, this study identified mix infection of three viruses in the field samples, including Newcastle disease, reovirus, and avian encephalomyelitis; however, it was negative for avian influenza and Marek’s disease viruses. Subsequently, the inoculation of several samples into embryonated chicken eggs confirmed the growth of these three viruses. As a consequence, disease control management should be conducted in the affected farms by implementing effective biosecurity and vaccination program.